Unfolding Stakeholders’ Engagement in the Design Process of National Common Agricultural Policy (CAP) Strategic Plans: Case of Lithuania - Živilė Gedminaitė-Raudonė; Vitalija Simonaitytė; Rita Lankauskienė (Agriculture)
Stakeholder engagement in the process of policy formation can mitigate the risks of flaws in policy planning and implementation; it also facilitates the successful adoption of new decisions, reduces conflict, and enhances the sense of responsibility among all actors involved in the implementation phase. Effective stakeholder engagement requires a multi-stakeholder approach, supported by cost-effective, bottom-up mechanisms that are tailored to stakeholders’ needs, experiences, and the challenges they face. This study examines the organisation and implications of stakeholder engagement in the process of Common Agricultural Policy (CAP) Strategic Plan (SP) formation in Lithuania. The research was conducted using qualitative methods. First, experts were selected through the quadruple helix approach, resulting in a total of 15 experts. Subsequently, a focus group was convened to deepen and expand our understanding of stakeholder engagement during the preparation of Lithuania’s Rural Development Programme 2023–2027. The focus group examined engagement in terms of the flexibility, transparency, inclusivity, and effectiveness of organisational and management practices. Analysis of stakeholders’ engagement in CAP SPs in Lithuania revealed that there is a certain middle ground between formalistic and more elaborated engagement.